New Reverse Die Variations from Selinus c. 440 BC - Kushnet , Marvin W. (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This paper reports two reverse dies from classical Selinus which, although previously published in trade, were incorrectly attributed to a similar but distinct issue. The first of these reverse dies is known from a single example published at auction. Another specimen of this specific reverse rests in private hands and, to my knowledge, has never before been published. The second reverse die is known from at least two examples which have appeared in commerce. This paper also describes the evolution of a distinctive die flaw corresponding to die state Q5β in Schwabacher’s catalog. This is found on the paired obverse of the newly described reverse issues.